2010
DOI: 10.1074/jbc.m109.086066
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to Oxygen

Abstract: The appearance of oxygen in the Earth's atmosphere via oxygenic photosynthesis required strict anaerobes and obligate phototrophs to cope with the presence of this toxic molecule. Here we show that in the anoxygenic phototroph Rubrivivax gelatinosus, the terminal oxidases (cbb 3 , bd, and caa 3 ) expand the range of ambient oxygen tensions under which the organism can initiate photosynthesis. Unlike the wild type, the cbb 3 ؊ /bd ؊ double mutant can start photosynthesis only in deoxygenated medium or when oxyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 35 publications
2
20
0
Order By: Relevance
“…Found only in prokaryotes, the bd-type oxidases are bioenergetically inferior to HCOs and thus generally play a minor role in aerobic respiration because they do not pump protons. By the same token, it serves as an O2 scavenger to inhibit degradation of O2-sensitive enzymes such as nitrogenase of Azorhizobium caulinodans and to support anaerobic photosynthetic growth of Rubrivivax gelatinosus (Kaminski et al, 1996;Hassani et al, 2010). The most prominent function of the bd-type oxidase is to facilitate pathogenic and commensal bacteria to colonize in O2-limited niches (Poole, 2005;Giuffrè et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Found only in prokaryotes, the bd-type oxidases are bioenergetically inferior to HCOs and thus generally play a minor role in aerobic respiration because they do not pump protons. By the same token, it serves as an O2 scavenger to inhibit degradation of O2-sensitive enzymes such as nitrogenase of Azorhizobium caulinodans and to support anaerobic photosynthetic growth of Rubrivivax gelatinosus (Kaminski et al, 1996;Hassani et al, 2010). The most prominent function of the bd-type oxidase is to facilitate pathogenic and commensal bacteria to colonize in O2-limited niches (Poole, 2005;Giuffrè et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The most prominent function of the bd-type oxidase is to facilitate pathogenic and commensal bacteria to colonize in O2-limited niches (Poole, 2005;Giuffrè et al, 2012). By the same token, it serves as an O2 scavenger to inhibit degradation of O2-sensitive enzymes such as nitrogenase of Azorhizobium caulinodans and to support anaerobic photosynthetic growth of Rubrivivax gelatinosus (Kaminski et al, 1996;Hassani et al, 2010). Our results demonstrated that the bd-type oxidase of S. oneidensis, consistent with its high affinity fort O2, plays a significant role in oxygen respiration under microaerobic but not aerobic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Cytochrome bd facilitates both pathogenic and commensal bacteria to colonize O 2 -poor environments [8689], serves as an O 2 scavenger to inhibit degradation of O 2 -sensitive enzymes such as nitrogenase [9098], and support anaerobic photosynthetic growth [99]. It is of interest to note that bd -type oxygen reductases predominate in the respiratory chains of bacteria that cause such diseases as bacillary dysentery [100], brucellosis [88,101], tuberculosis [87], pneumonia, life-threatening sepsis, meningitis [102], as well as Salmonella [103,104], Bacteroides [86], and Listeria monocytogenes [105] infections.…”
Section: Physiological Functionsmentioning
confidence: 99%
“…Genetic analyses showed that caa 3 is not active in the wild type background. However, a mutant (Res2) that expresses only caa 3 was isolated and characterized (15). A ccoI gene homologue encoding a putative P1B-type ATPase was identified in the vicinity of the cbb 3 -encoding operon.…”
mentioning
confidence: 99%